2023
DOI: 10.1002/adfm.202305880
|View full text |Cite
|
Sign up to set email alerts
|

Injectable Shear‐Thinning Hydrogels with Sclerosing and Matrix Metalloproteinase Modulatory Properties for the Treatment of Vascular Malformations

Fatemeh Zehtabi,
Ankit Gangrade,
Kaylee Tseng
et al.

Abstract: Sac embolization of abdominal aortic aneurysms (AAAs) remains clinically limited by endoleak recurrences. These recurrences are correlated with recanalization due to the presence of endothelial lining and matrix metalloproteinases (MMPs)‐mediated aneurysm progression. This study incorporates doxycycline (DOX), a well‐known sclerosant and MMPs inhibitor, into a shear‐thinning biomaterial (STB)‐based vascular embolizing hydrogel. The addition of DOX is expected to improve embolizing efficacy while preventing end… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
6
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 44 publications
(56 reference statements)
2
6
0
Order By: Relevance
“…Given the comparatively high death rate (46%) among patients with ECF due to intra-abdominal bleeding reported by Wu et al in their retrospective study, 47 a thorough evaluation of the biomaterial's impact on blood coagulation in the context of ECF is crucial. Laponite and gelatin are known for their ability to clot blood, 6,28 aligning with our observation of D5L4P0, which relatively reduced blood clotting time to 20% (Figure 3Cii). However, adding PRP reduced the hemostatic effects of D5L4P0 hydrogel, and D5L4P25 showed no significant reduction in blood clotting time.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…Given the comparatively high death rate (46%) among patients with ECF due to intra-abdominal bleeding reported by Wu et al in their retrospective study, 47 a thorough evaluation of the biomaterial's impact on blood coagulation in the context of ECF is crucial. Laponite and gelatin are known for their ability to clot blood, 6,28 aligning with our observation of D5L4P0, which relatively reduced blood clotting time to 20% (Figure 3Cii). However, adding PRP reduced the hemostatic effects of D5L4P0 hydrogel, and D5L4P25 showed no significant reduction in blood clotting time.…”
Section: ■ Results and Discussionsupporting
confidence: 89%
“…The shear-thinning behavior of the DLP hydrogel aligns with previous reports on Laponite hydrogel. 6,28,29 Additionally, the addition of PRP did not alter this behavior (Figure 2F).…”
Section: ■ Results and Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…Recently, extensive research has been conducted on gelatin for the development of injectables aimed at treating hemorrhage. Gelatin has been explored as a shear-thinning, semisolid, , and cross-linkable hydrogel. , These studies have been motivated by the various characteristics of gelatin, such as its ability to trigger clot formation, low immunogenicity, and support for cell attachment and proliferation. Among these approaches, injectables composed of gelatin and nanoclay have shown promising results in hemorrhage control and embolization. , However, it has been reported that silicate nanoplatelets can induce cytotoxicity through the generation of reactive oxygen species, damage to cell membrane interactions, and intracellular interaction mechanisms …”
Section: Introductionmentioning
confidence: 99%